SENYAWA DAN AKTIVITAS ANTIMIKROBA GOLONGAN ASAM LEMAK DAN ESTERNYA DARI TANAMAN - Murhadi Murhadi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2009)
Problems in food preservation have grown to be more complex as new food products are continuously introduced onto the market. They require longer shelf life and greater assurance of protection from microbial spoilage. There are several chemicals that can be used as antimicrobial agents. For instance, acetic acid and sulfur dioxide are widely used as food preservatives. However, these chemicals required caution in handling since they are corrosive and their vapors can irritate the eyes and respiratory tract. Although conventional synthetic antimicrobial agents have excellent activities, their safety in human body has been considered doubtful. Since it is known that antimicrobial agents are contained in natural materials, many research studies have been carried out to improve the shelf stability of foods and cosmetics using natural antimicrobial agents. Many naturally occurring compounds found in edible and medicine plants, herbs, and spices have been shown to possess antimicrobial function and could serve as a source of antimicrobial against food pathogens. Recently the interest in the biological activities of plant extracts has been rekindled and has been the subject of intense scientific investigation. Fatty acid and its ester forms as monoglyceride and or diglyceride of plant materials, especially from palm kernel oil and coconut oil such as lauric acid (12:0), miristic acid (14:0) and capric acid (10:0) have antimicrobial function. The antimicrobial activities of monolaurin, monomiristin and or monocaprin and its diglyceride’s forms are well recognized and showed a wide spectrum of antimicrobial activities toward several microbes. Keywords: Fatty acids, monolaurin, monomiristin, monocaprin, antimicrobial activities